Policy recommendations on the gender effects of changes in tax bases, rates, and units: Results of microsimulation analyses for six selected EU member countries - Marian Fink; Jitka Janová; Danuše Nerudová; Jan Pavel; Margit Schratzenstaller; Friedrich Sindermann-Sienkiewicz; Martin Spielauer (Austrian Institute of Economic Research (WIFO), 2019)
The design of tax systems has a considerable impact on the distribution of income and wealth at the household and the individual level, and due to gender-differentiated socio-economic conditions also in a gender perspective. One of the most important areas of taxation is the taxation of personal incomes. Besides the level of income tax rates and the design of the income tax schedule (progressive versus flat tax schedule), the system of household taxation (joint versus individual taxation), the determination of taxable income and the design of tax exemptions (tax allowances versus credits), particularly child-related ones, are crucial determinants of the distributional effects and work incentives of the personal income tax. The study presents an overview of the microsimulation results for selected provisions of the personal income tax system on income distribution and work incentives. The microsimulations are based on EUROMOD for six selected EU countries: Germany, Austria, Spain, Czech Republic, UK, and Sweden, countries of different "families" of welfare and taxation traditions.
Keywords: D31; H21; H24; J16; 330; EUROMOD; microsimulations; gender effects; income taxation